Compressive sensing holography based on optical heterodyne detection. (December 2016) - Hu, Youjun; Zhou, Dingfu; Yuan, Sheng; Wei, Yayun; Wang, Mengting; Zhou, Xin
Abstract: In this paper, compressive sensing holography based on optical heterodyne detection is presented, which can photograph the hologram of an object. The complex hologram is composed of a sine-hologram and a cosine-hologram. A single pixel photoelectric conversion element is used to detect the time-varying optical field which contains the amplitude and phase information of the transmitted light, and a simulation result is demonstrated further by recording the Fresnel hologram of a complex amplitude object. Highlights: Hologram of an object can be obtained by optical heterodyne detection and compressive sensing holography (CSH). Impact of twin-image, zero-order terms and speckle noise can be successfully avoided. Data volume of hologram is greatly decreased due to the use of compressive sensing. Recording process is speedier than that of phase-shifting CSH, so the stability requirement of surrounding can be reduced. Optical heterodyne detection CSH is potential and practical in hologram recording field.